Impact of new media towards traditional journalism / Sharifah Izlin Natasya Syed Abdul Aziz, Mohammad Umair Mohammed Yuzri and Aiman Hariz Azlin - Syed Abdul Aziz, Sharifah Izlin Natasya; Mohammed Yuzri, Mohammad Umair; Azlin, Aiman Hariz (2018)
The verb "impact" has developed the transitive sense "to have an impact or effect on". Impact is something that has to do on a situation, process or a person is a sudden and powerful effect that it has on them (Collins English Dictionary, n.d). The history of "traditional journalism" has been described as the emergence of a professional identity of journalists with claims to an exclusive role and status in society (Mark Deuze, 2005). Technologies described as the "new media" are mostly digital and are likely to describe as the subject matter made available using different forms of electronic communication (Lev Manovich, n.d). The researchers are focusing on the impact of new media towards traditional journalism. The research objective for this study are: • To determine the effects of new media towards traditional journalism. • To identify the ways that new media has transformed traditional journalism into. • To analyse the solution that can be made in order to make traditional journalism as the new easy access to new media.